ANALISIS KEBERLANJUTAN WISATA KOTA MELALUI PENDEKATAN COMMUNITY BASED TOURISM DI YOGYAKARTA - Hery Susanto; Murtiadi Awaluddin (Kepariwisataan: Jurnal Ilmiah, 2026)
AbstractThis study aims to analyze the condition of sustainable city tourism in Yogyakarta, identify the role and contribution of Community Based Tourism (CBT) in supporting the sustainability of city tourism, and formulate a strategy for developing sustainable city tourism through the Community Based Tourism (CBT) approach in city tourism destinations in Yogyakarta. This type of research is descriptive research with a mixed method approach. The population in the study were tourism managers, local communities, tourists, and local governments. Samples were taken using purposive sampling, including 20 tourism managers, 50 local communities, and 50 tourists from each location. Data were obtained through primary data, namely in-depth interviews, questionnaires, and direct observation, and secondary data from official documents, government reports, and literature studies. The results of the study indicate that the sustainability of city tourism in Yogyakarta is in the fairly good category but not yet optimal. The principle of Community Based Tourism (CBT) has been applied in several aspects, such as community involvement in tourism program planning and providing opportunities for women's roles in managing tourism businesses. Based on field findings, there are five main strategies that need to be implemented to improve the sustainability of city tourism through CBT in Yogyakarta, iincreasing community involvement, strengthening transparency and equitable distribution of economic benefits, sustainable training and capacity development, strengthening local cultural preservation and measured and sustainable environmental management.Keywords: Tourism Sustainability; Community Based Tourism; Development StrategyAbstrakPenelitian ini bertujuan untuk menganalisis kondisi keberlanjutan wisata kota di Yogyakarta, mengidentifikasi peran dan kontribusi Community Based Tourism (CBT) dalam mendukung keberlanjutan wisata kota dan merumuskan strategi pengembangan wisata kota berkelanjutan melalui pendekatan Community Based Tourism (CBT) pada destinasi wisata kota di Yogyakarta. Jenis penelitian ini penelitian deskriptif dengan pendekatan mixed method. Populasi dalam penelitian yaitu pengelola wisata, masyarakat lokal, wisatawan, dan pemerintah daerah. Sampel diambil menggunakan purposive sampling, mencakup 20 pengelola wisata, 50 masyarakat lokal, dan 50 wisatawan dari masing-masing lokasi. Data diperoleh melalui data primer yaitu wawancara mendalam, kuesioner, dan observasi langsung dan data sekunder dari dokumen resmi, laporan pemerintah, dan studi literatur. Hasil penelitian menunjukkan bahwa keberlanjutan wisata kota di Yogyakarta berada pada kategori cukup baik namun belum optimal. Prinsip Community Based Tourism (CBT) telah diterapkan di beberapa aspek, seperti pelibatan masyarakat dalam perencanaan program wisata dan pemberian kesempatan peran perempuan dalam pengelolaan usaha wisata. Berdasarkan temuan lapangan, terdapat lima strategi utama yang perlu dilakukan untuk meningkatkan keberlanjutan wisata kota melalui CBT di Yogyakarta yaitu meningkatkan keterlibatan masyarakat, memperkuat transparansi dan pemerataan manfaat ekonomi, pelatihan dan pengembangan kapasitas berkelanjutan, penguatan pelestarian budaya lokal dan pengelolaan lingkungan yang terukur dan berkelanjutan.Kata Kunci: Keberlanjutan Wisata; Community Based Tourism; Strategi Pengembangan